Green synthesized silver nanoparticles: Optimization, characterization, antimicrobial activity, and cytotoxicity study by hemolysis assay - Liaqat, Nida; Jahan, Nazish; Khalil-ur-Rahman,; Anwar, Tauseef; Qureshi, Huma (Frontiers in Chemistry, 2022)
Green nanotechnology has emerged as a viable option for the production of nanoparticles. The goal of current experiments was to make AgNPs using Eucalyptus camaldulensis and Terminalia arjuna extracts, as well as their mixtures as green reducing and capping agents. The conditions for maximal yields, regulated size and stability of silver nanoparticles (concentration of silver nitrate solution and plant extract, time, pH, temperature) were tuned. The production of AgNPs was confirmed using a UV–Vis spectrophotometer and the surface plasmon resonance band (SPR). With the help of a zeta sizer and a scanning electron microscope, the size, shape, and stability of these were determined. The biomolecules responsible for the reduction of silver ion (Ag+) and the stability of silver nanoparticles generated with the examined plants were identified using FTIR analysis. Bascillus subtilis, Staphylococcus aureus, Pasteurella multocida and Escherichia coli bacterial strains were used by using well diffusion method to test the antimicrobial capability of biosynthesized nanoparticles. When 1mM AgNO3 was added to plant extracts and incubated for 60 minutes at 75°C in neutral medium, maximal nanoparticles were produced. Biosynthesized silver nanoparticles were stable, spherical, and monodispersed, according to zeta potential and SEM examination. Silver nanoparticles synthesized with Combination 2 and T. arjuna showed highest zone of inhibition (16mm) against B. subtilis while combination 3 showed largest zone of inhibition against S. aureus. Greenly produced silver nanoparticles showed good antibacterial activity while causing negligible cytotoxicity.